DEVELOPING A BEST PRACTICE-BASED OCCUPATIONAL SAFETY AND HEALTH MODULE FOR VOCATIONAL STUDENTS - Randyputra, Bofit Osbron; Suryanto, Ahmad Eko; Pancawati, Ratna (Universitas Pendidikan Indonesia, 2025)
This study aims to develop a best practice-based Occupational Safety and Health teaching module and evaluate its feasibility for vocational students in Light Vehicle Engineering. This research employed the Research and Development method with an ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The subjects included a material expert (vocational teacher), a media expert (instructional media lecturer), and 35 students. Data were collected using expert validation questionnaires and student response surveys with a Likert scale, then analyzed using quantitative descriptive statistics. The results indicated high feasibility in content, with the material expert validation reaching 82.67% (Very Feasible) and student responses scoring 84.57% (Very Feasible). The findings highlight that the module's content is highly relevant and contextually beneficial for students. However, the media expert validation only scored 65.33% (Feasible), indicating significant weaknesses in visual design, graphics quality, and layout. This study concludes that for vocational students, the relevance and practical utility of content are more dominant factors in the acceptance of a teaching module than its aesthetic appeal. Nevertheless, improvements in media design are necessary to achieve optimal learning effectiveness.